Redox Reaction Triggered Nanomotors Based on Soft-Oxometalates With High and Sustained Motility - Mallick, Apabrita; Laskar, Abhrajit; Adhikari, R.; Roy, Soumyajit (Frontiers in Chemistry, 2018)
The recent interest in self-propulsion raises an immediate challenge in facile and single-step synthesis of active particles. Here, we address this challenge and synthesize soft oxometalate nanomotors that translate ballistically in water using the energy released in a redox reaction of hydrazine fuel with the soft-oxometalates. Our motors reach a maximum speed of ̴ 370 body lengths per second and remain motile over a period of approximately three days. We report measurements of the speed of a single motor as a function of the concentration of hydrazine. It is also possible to induce a transition from single-particle translation to collective motility with biomimetic bands simply by tuning the loading of the fuel. We rationalize the results from a physicochemical hydrodynamic theory. Our nanomotors may also be used for transport of catalytic materials in harsh chemical environments that would otherwise passivate the active catalyst.